PERAN PENDIDIKAN AGAMA TERHADAP TUMBUH KEMBANG ANAK ABAD 21 - Arief Hidayat Afendi (Risâlah, Jurnal Pendidikan dan Studi Islam, 2018)
As the Prophet says: "Teach the children to live in their day." Technological developments seem to be the challenge of parents in this century. Who is able to develop himself with the pattern of life today, then he is the one who will succeed in doing perfect religious education for children. Conversely, who is left then he who will get a failure in supervising the growth of his child. The global discussion in this paper 1) How the influence of religious education on child growth 2) How the role of parents in supervising the children in the use of gadgets. Reseach Method used is descriptive analytical with qualitative method that is collecting data in the form of qualitative and quantitative data from review of data and library that relevant to case become object of discussion. Keywords: Education, Religion, Growing Up.